Seasonal influenza vaccination of high-risk adults. (1st December 2016) - Loubet, Paul; Loulergue, Pierre; Galtier, Florence; Launay, Odile
ABSTRACT: Introduction : Adults at a high risk of severe influenza, because of their age and/or underlying health disorders, should receive seasonal influenza vaccination in order to reduce the incidence of severe illness and premature death. However, because current influenza vaccines are perceived to have suboptimal efficacy, vaccine coverage is below the recommended level in this population. Areas covered : This review examines, for each high-risk group, available data on influenza infection, vaccine efficacy and safety, and vaccine coverage. We conducted a literature search in the PubMed database to identify randomized controlled trials, observational studies and reviews published from 2000 through 2015 on both seasonal and pandemic influenza. Only studies published in English were considered. While the topic of this review is seasonal influenza, data on pandemics are included when relevant. Expert Commentary : Current seasonal influenza vaccines are only moderately protective, and vaccines eliciting broader and more durable immunity are therefore needed. Research on the use of higher doses, adjuvants, and a universal influenza vaccine is ongoing. Influenza vaccine coverage needs to be increased. Vaccination of contacts of high-risk individuals, including healthcare workers, should be encouraged.